2020
DOI: 10.1080/10494820.2020.1830121
|View full text |Cite
|
Sign up to set email alerts
|

Fear from COVID-19 and technology adoption: the impact of Google Meet during Coronavirus pandemic

Abstract: This study seeks to explore the effect of fear emotion on students' and teachers' technology adoption during COVID-19 pandemic. The study has made use of Google Meet© as an educational social platform in private higher education institutes. The data obtained from the study were analyzed by using the partial least squares structural equation modeling (PLS-SEM) and machine learning algorithms. The main hypotheses of this study are related to the effect of COVID-19 on the adoption of Google Meet as COVID-19 rise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
128
2
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 199 publications
(196 citation statements)
references
References 52 publications
17
128
2
13
Order By: Relevance
“…Our analysis strongly supported the proposed research model. The findings of other researchers [23,41,[43][44][45][47][48][49][50][56][57][58]63] and our results have similarities.…”
Section: Principal Findingssupporting
confidence: 86%
See 1 more Smart Citation
“…Our analysis strongly supported the proposed research model. The findings of other researchers [23,41,[43][44][45][47][48][49][50][56][57][58]63] and our results have similarities.…”
Section: Principal Findingssupporting
confidence: 86%
“…Our hypotheses (ie, H1, H5 and H6) significantly and positively supported the relationships between the SN and PEOU (P=.001), the SN and PU (P=.03), and the SN and PF (P=.04). Numerous research studies have assessed the relationship between the SN and PEOU, the SN and PU, and the SN and PF [23,41,[43][44][45]. Moreover, our analysis provided empirical evidence for the effect of the PEOU on PU, as proposed in hypothesis H2.…”
Section: Principal Findingssupporting
confidence: 58%
“…The fear factor was tackled in recent studies by [27] as an external factor that affects students' perception of technology during the pandemic. The fear from COVID-19 is manifested in forms such as threat, anxiety, feeling of uncertainty, the risk for loved ones [19,[28][29][30][31][32].…”
Section: Perceived Fearmentioning
confidence: 99%
“…Previous studies have confirmed a relationship between health anxiety or fear emotion and using healthrelated technologies. Al-Maroof et al (2020) [4] found a significant effect of fear emotion related to Google Meet adoption during COVID-19. Wnuk et al (2020) [5] revealed that an adoption of COVID-19 tracking technologies was significantly predicted by users' perceived personal threat and lack of personal control.…”
Section: -Introductionmentioning
confidence: 99%